Maqāmāt dan Aḥwāl dalam Tasawuf - Media Zainul Bahri (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2004)
This writing presents the concepts of “maqāmāt” and “aḥwāl” in Sufism. “Maqāmāt” refers to the creative spiritual path undertaken by Sufis to approach and encounter God. It (maqāmāt) must be strived for (makāsib) with the entirety of one’s soul and body. True to its name, it is fixed and permanent. On the other hand, “aḥwāl” are the mental and spiritual states experienced by Sufis as a result of “maqāmāt.” It is considered a divine gift (mawāhib), cannot be attained through effort, and is subject to change. However, in the view of some Sufi groups, both are considered gifts.